Addiction Recovery, Gardening, and Faith: The Garden of Allan (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2017)
The Garden of Allan is far from the Garden of Eden, but God, the first and ultimate gardener is there. Teen Challenge (TC), a faith-based, residential drug and alcohol rehabilitation program on 10 acres of land in rural Saskatchewan near the town of Allan. What began with a simple church bulletin, with a notice saying that Teen Challenge needed donations of fruits and vegetables lead to the development of an active gardening and food project at the centre. What could have been a simple donation developed into a project that has dramatically changed the life of the volunteer coordinator, and the lives of several students in the program. In addition to developing their faith, and using their faith to overcome their addictions, the TC program emphasizes community living, life skills, health and recreation, music, art, and character development. Gardening and food related activities are valuable life skills, are part of a healthy and healing lifestyle, and further develop the student’s faith. Gardening activities can be extremely therapeutic in relieving stresses including depression and anxiety, which are common in the lives of those struggling with alcohol and drug addiction. Gardening can also be extremely rewarding, yielding food for sustenance, success, achievement, validation, and prayers answered. In the Garden of Allan, gardening is both indoor and outdoor. During inclement times of the year, the students grow nutrient dense microgreens that are proven beneficial in repairing damage caused by drugs and alcohol. The Garden of Allan is where faith and gardens grow.